SUSTAINABLE AGRICULTURAL FINANCE IN DEVELOPING COUNTRIES: TRENDS, COLLABORATIONS, AND FUTURE PATHWAYS - Muhammad Sheeraz; Kanwal Iqbal Khan (Journal of Animal and Plant Sciences, 2026)
Sustainable Agricultural Finance (SAF) is an increasingly important area of research, especially in developing countries where agriculture is the backbone of food security, poverty alleviation and environmental sustainability. Lack of previous studies has resulted in a failure to provide sufficient guidelines on how SAF research has developed in developing countries and the thematic gaps that remain unfilled. Bibliometric techniques provided the framework for the study to explore the key questions. Data was collected from the Scopus database from 1983 to 2025. The results indicate an increase in scholarly interest in SAF through an increase in publications, citations and international collaboration as well as the integration of finance, sustainability and policy frameworks in the agricultural sectors of developing countries. Moreover, 'sustainability' emergence most important source, and South Africa has been revealed as the main contributor and collaborator. The results also reveal six types of themes: rural finance, smallholder inclusion, agroecology, patterns of environmental change, and linkages to global policies. Several pathways can be explored in future research including gender-inclusive finance, tools to gauge climate risk, and new funding transport mechanisms. The study broadens insights into overlooked areas and indicates possible future research paths, which serve as a guide to aid policymakers, researchers, and practitioners, aiming to strengthen sustainable agricultural financing throughout the Global South.
Keywords: Sustainable Agricultural Finance; Developing Countries; Rural Finance; Environmental Change; Gender-inclusive Finance; Economic development